THE URGENCY OF ELECTRONIC WASTE MANAGEMENT REGULATION IN INTERNATIONAL AND REGIONAL (ASEAN) LAW WITH ENVIRONMENTAL PROTECTION APPROACH - Nadya Meta Puspita (Padjadjaran Journal of International Law, 2019)
AbstractThe development of technology has been increasing rapidly thus almost all aspects of humans are supported by technology and electronic equipment. More electronic wastes are produced, but those could not be managed similar to the conventional wastes and do not have the same characteristics as hazardous wastes as regulated in the Basel Convention 1989 so that the Convention cannot be applied to electronic wastes management optimally. In this present time, there are still no instruments in international law regarding the management of electronic wastes, but the international community has begun to discuss this issue and argue that it is necessary to develop regulations in international and regional levels, especially in the ASEAN region. The analysis and conclusions of this research shows that the Basel Convention cannot optimally accommodate the regulation of electronic wastes management and it is necessary to establish a regulation in the form of a mechanism under the Basel Convention 1989 with regard to environmental aspects. Arrangements at the ASEAN regional level should be made by referring to the principles regulated in the mechanism and formed in a coordinative and non-coercive guideline. Keywords: e-waste, e-waste management, environmental protection AbstrakTeknologi semakin berkembang hampir semua aspek kehidupan manusia telah didukung oleh teknologi dengan peralatan elektronik. Produksi sampah elektronik semakin banyak, namun mereka tidak dapat dikelola seperti sampah konvensional dan juga tidak sepenuhnya memiliki karakteristik yang sama seperti sampah B3 yang telah diatur dalam Konvensi Basel 1989 sehingga Konvensi tidak dapat diterapkan pada pengelolaan sampah elektronik secara optimal. Saat ini, belum ada instrumen dalam hukum internasional mengenai pengelolaan sampah elektronik, namun masyarakat internasional sudah mulai membahas isu ini dan perlu adanya untuk mengembangkan peraturan di tingkat internasional dan regional, khususnya di ASEAN. Analisis dan kesimpulan penelitian ini memperlihatkan pengaturan dalam Konvensi Basel 1989 tidak dapat mengakomodasi secara optimal mengenai pemanfaatan sampah elektronik sehingga perlu dibuat suatu peraturan berupa mekanisme di bawah Konvensi Basel 1989 dengan memperhatikan aspek-aspek lingkungan. Pengaturan di tingkat regional ASEAN dapat dibuat dengan mengacu pada prinsip-prinsip yang diatur dalam mekanisme tersebut namun dibentuk berupa panduan yang lebih koordinatif dan tidak memaksa. Kata kunci: sampah elektronik, pengelolaan sampah elektronik, perlindungan lingkungan